Molecular fractionation and sub-nanoscale distribution of dissolved organic matter on allophane. Issue 7 (7th June 2019) - Ding, Yang; Lu, Yang; Liao, Peng; Peng, Shimeng; Liang, Yuzhen; Lin, Zhang; Dang, Zhi; Shi, Zhenqing
Abstract : We elucidated the spatial distribution of DOM on allophane and the mechanisms controlling the adsorptive fractionation of DOM molecules. Abstract : Allophane, a nano-size alumino-silicate mineral, has a peculiar hollow and spherical nanostructure with diameters of 3.5–5 nm and some defects or open pores. The adsorptive fractionation of dissolved organic matter (DOM) within allophane nanostructures is a key soil process affecting carbon cycling in soil environments, but the underlying mechanisms are poorly understood. In this study, we employed both double spherical-aberration-corrected scanning transmission electron microscopy (Cs-STEM) and Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) to elucidate the spatial distribution of DOM on allophane at sub-nanoscales and the mechanisms controlling the adsorptive fractionation of DOM molecules. Copper titration experiments and WHAM 7 were used to assess the role of carboxylic groups in the fractionation of DOM on allophane. Cs-STEM results revealed that within allophane aggregates, C mainly distributed on the edges of the pore spaces between allophane aggregates while some DOM molecules localized at some small pore spaces. Moreover, the Cs-STEM results suggested that DOM molecules were able to enter the interior spaces within tiny allophane nanoparticles/aggregates. FT-ICR-MS analysis indicated that molecules with high aromaticity, oxygen numbers and amounts of COO groups were preferentially adsorbed. The results of Cu titration and WHAM 7 calculations indicated that the carboxylic functional groups of DOM were selectively removed from solutions during adsorptive fractionation. Overall, both chemical adsorption and physical isolation may be responsible for the strong sequestration of DOM molecules on allophane. Our results contribute to prediction of C cycling in the environment.